Research on Digital Transformation of Corporate Legal Services under the Background of Internet+ - Zhai, Quanquan (International Journal of Social Sciences and Public Administration, 2024)
With the rapid advancement of internet technology, industries across the board are embracing digital transformation, and the corporate legal services sector is no exception. In the context of the "Internet +" era, the digital transformation of corporate legal services is not only an inevitable trend but also a crucial pathway to enhancing the efficiency and quality of legal services. This article explores the current state of corporate legal services in the digital age, the major challenges faced, and the strategies for addressing them. By examining the introduction of legal tech tools, the refinement of legal and policy frameworks, internal organizational changes, and the optimization of client experience, this article aims to provide comprehensive guidance and reference for the digital transformation of corporate legal services.